Multi-point collaborative authentication method based on user image intelligent collection in the internet of things - Li, Yunfa; Tu, Yifei; Lu, Jiawa (MDPI AG, 2019)
With the increasing demand for intelligent services of the Internet of Things (IoT), its security issues have attracted widespread attention recently. Since most of the existing identity authentication policies are based on a single authentication mode, they are highly likely to cause problems such as illegal operation and stealing of sensor information. In order to meet the needs of increasing IoT users for the security management of intelligent services, a multi-point collaborative authentication method based on user image intelligent collection for the security problems faced by IoT in identity authentication is proposed in the paper. This method firstly collects the identity of the legal user through the intelligent collection technology and then realizes the identity authentication of the unidentified user through the collaborative authentication between the local domain management machine, the back-end image management machine, and the cloud server. Compared with the traditional single identity authentication method, our method uses three-party collaborative authentication to avoid the problem of sensor information stealing easily caused by a single authentication method, which makes the user’s identity authentication more secure and effective. The security analysis shows that the method is able to resist multiple attacks and prevent the sensor information from being illegally operated and stolen, protecting the security of the sensor information.